Does Productivity Growth Lead to Appreciation of the Real Exchange Rate? - Lee, Jaewoo (IMF Working Papers; Working Paper, 2003)
We revisit the time-honored link between productivity and the real exchange rate. Consistent with the traditional view, we find that higher labor productivity tends to lead to appreciation of the real exchange rate. Contrary to the traditional view, however, we find that the positive productivity effect is transmitted through the real exchange rate based on tradable prices, rather than through relative prices between tradables and nontradables. Moreover, higher total factor productivity is found, if anything, to lead to depreciation of the real exchange rate. These last two pieces of evidence provide support for the emerging view that limited tradability of goods and services provides scope for the strategic pricing decision, which has material consequences for the aggregate real exchange rate.